Impact of Emotional Intelligence on Job Performance of Nurses with the Mediating Effect of Job Satisfaction - Richa Chauhan; Vidhi Kaul; Nidhi Maheshwari (ACHSM, 2022)
The current study investigates the effect of Emotional Intelligence (EI) on the performance of nurses with the mediating effect of job satisfaction. This study measures the concept of EI, Job Performance, and Job Satisfaction across 385 respondents from various private and government hospitals and the locale of the study was the Delhi NCR region. PLS-SEM was used for analyzing the data. The result indicates that a relationship exists between these three variables and job satisfaction mediates the relationship between Emotional Intelligence & Job performance. The findings of the current study showed that awareness of emotions, regulation of emotions, and managing of emotions are the significant components of EI which enhances leadership, critical care, professional development, interpersonal relationships, planning and collaboration aspects of Job Performance. Further, the mediating effects support that the positive working conditions and organizations' compensation policy fetches higher level of Job Satisfaction among the professional and nursing employees who are satisfied as well as having a higher level of Emotional Quotient would be a better performer than the employees who are having a low level of emotional intelligence. It can be recommended that while recruiting nursing employees along with their technical competence EI competence needs to be equally emphasized. Similarly, EI needs to be integrated into healthcare practice guidelines and performance evaluations as it is one of the important assets of individual persona.